IDENTIFIKASI TENTANG PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI PADA KELAS XI IPS SMA NEGERI 1 DRIYOREJO GRESIK - SITI SHOLIHAH (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This research aims to determine the materials used in the teaching of accounting in class XI IPS and the reasons teachers use the teaching materials, In addition, to determine the feasibility of teaching materials used in the teaching of accounting in class XI IPS Driyorejo SMAN 1 Gresik. This research is descriptive quantitative approach. Techniques of data collection of this research through interviews, documentation, and review of teaching materials expert. The results showed that materials used in the form of text books with titles Ekonomi Untuk SMA dan MA kelas XI with the publisher Esis. Reason for the selection of instructional materials for more economical and practical. Feasibility of teaching materials obtained an average percentage of 84.08% with a very decent criteria. Keywords: Teaching Materials, Text Books